2018
DOI: 10.1037/cpp0000202
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of combined medical and behavioral treatments for constipation within a specialty outpatient clinic.

Abstract: Chronic constipation is a common and challenging childhood problem. Effective treatment for chronic constipation and fecal incontinence includes a combination of medical and behavioral treatments. This study evaluates the outcomes associated with providing these treatments in a specialty outpatient clinic consisting of a nurse practitioner and behavioral psychologist. Fifty-seven patients were followed up for initial and follow-up appointments in this multidisciplinary chronic constipation clinic. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Six studies (6%) included in this synthesis had a clear and explicit equity focus 143,271,282,[300][301][302] ; 13 studies (12%) partially addressed equity in their study. 24,102,103,145,144,255,261,[303][304][305][306][307][308][309][310][311][312][313][314][315][316][317] Age and sex were the most commonly reported factors; few studies reported any other social determinant factors.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies (6%) included in this synthesis had a clear and explicit equity focus 143,271,282,[300][301][302] ; 13 studies (12%) partially addressed equity in their study. 24,102,103,145,144,255,261,[303][304][305][306][307][308][309][310][311][312][313][314][315][316][317] Age and sex were the most commonly reported factors; few studies reported any other social determinant factors.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Sixty-five studies described evidence uncertainties and a limited evidence base as a significant barrier to implementation. 63,64,69,74,84,92,102,103,119,132,133,136,143,145,149,153,154,161,174,178,185,203,211,214,232,243,255,258,270,282,302,303, Evidence was reported as hampered by variation in diagnostic assessment and inconsistent application of CFC definitions, different outcomes, poor adherence, small sample sizes and general lack of high-quality studies.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…Most toileting interventions prescribed for FE require constant adult monitoring and prescribed regular defecation attempts, regardless of whether the child feels an urge to defecate, particularly after surgery to correct HD problems. Sometimes this can only happen through enrollment in an outpatient or inpatient behavioral treatment program where treatment can be monitored by nurse practitioners and/or behavioral psychologists (e.g., see Hankinson et al, 2018).…”
Section: Social-emotional and Behavioralmentioning
confidence: 99%
“…Prior research has demonstrated benefits of integrated medical and behavioral treatment in functional constipation in naturalistic studies (e.g. Hankinson et al, 2018; Stark et al, 1997) and randomized control trials (e.g., Cox et al, 1998). The most recent clinical guidelines published by the North American Society of Pediatric Gastroenterology, Hepatology, and Nutrition (NASPGHAN) recommend both medication and psychological intervention strategies including, “demystification, explanation, and guidance for toilet training” (Tabbers et al, 2014).…”
mentioning
confidence: 99%